(untitled) (Scientific Journal of Research Studies in Future Psychology, 2025)
Objective: The present study aimed to investigate the effect of cognitive–emotional mindfulness training on reducing the intensity and frequency of obsessive thoughts among urban adults aged 18–35. Methods: This semi-experimental study employed a pretest–posttest control group design. The statistical population included urban adults residing in Tehran. Sixty participants with elevated Yale–Brown Obsessive–Compulsive Scale (Y-BOCS) scores were selected and randomly assigned to experimental (n=30) and control (n=30) groups. The experimental group participated in eight weekly sessions of cognitive–emotional mindfulness training focused on mindful attention, cognitive emotion regulation, and breathing awareness exercises, while the control group received no intervention. Data were analyzed using independent t-tests, ANCOVA, and repeated measures ANOVA.Results: The results indicated a significant reduction in the intensity and frequency of obsessive thoughts in the experimental group compared to the control group (p<0.01). Moreover, the effect persisted over time according to the follow-up trend analysis.Conclusion: Cognitive–emotional mindfulness training effectively enhances emotional regulation and awareness of intrusive thoughts, leading to decreased obsessive patterns and improved psychological adjustment in urban adults.